Pengembangan Bahan Ajar Sintaksis Arab (Nahwu 2) dengan Pendekatan Kontekstual Budaya Lokal Berbasis Wisata Nusantara pada Perguruan Tinggi - Hendrawanto Ch; Indri Susilowati (Universitas Negeri Jakarta, 2018)
Character education should be based on one’s own culture, in the form of excavation of noble values ​​that exist in local wisdom. Character values ​​internalized by character traits should be taken through local noble values ​​and culture as the basis and basis for character education. This is in line with UNESCO’s recommendations in 2009. The method used in this research is a quantitative descriptive research method to explain the research results of the development of Arabic syntactic (naḥwu 2) teaching material with a contextual approach to local culture with the theme of Nusantara tourism to improve Arabic language skills for students of Arabic Language Education Study Program, Universitas Negeri Jakarta. Based on the results of research conducted on the development of this teaching material, there are several aspects of the assessment of expert examiners with the following assessment: assessment of material experts 82,8%, linguists 85,8%, media experts 83,85%. From these three experts, an average value of 84,15% was obtained, which means Arabic syntactic (naḥwu 2) teaching materials with a contextual approach to local culture with the theme of Nusantara tourism received scores with good criteria and were suitable for use in teaching Arabic syntax in higher education.